THE ROLE OF RAINFALL AND BASEFLOW FOR FLOOD EVENT AT JAKARTA (Case Study: November 2010-1013) - PUJI KHOMEINI (NIM : 12811033), SHARAH
Jakarta is a vulnerable region of flood where it happens almost every year in Jakarta. The Indonesian National Board for Disaster Management (BNPB) statistics result showed the flood occurs mostly in November, January, and February. Rainfall is one matter that causes the flood. Researches showed the largest amount of monthly rainfall and baseflow occurs in December and January. Therefore more researches are needed especially in the context of what caused a large amount of monthly rainfall in November, whether it is caused by the increasing of the baseflow or not. There are lots of methods found in order to separate the baseflow, includes Recursive Digital Filter (RDF) methods, and than count CDF value for extreme value with Cumulative Distribution Function (CDF). Result shows that the Cumulative Distribution of baseflow in November period 2008-2013 not showing baseflow extreme condition with value 17,61 m3/s, where the baseflow in November is lower than other months. The calculation of Direct Run-Off (DRO) in November shows a high value after in January and February. The daily maximum rainfall in November shows a high value 59,53 mm particularly in the peak of streamflow in 2012. Therefore, the extreme flood occurs in November in Jakarta was not caused by the extreme baseflow but by the high Direct Run-Off caused by extreme rainfall. Moreover, there was a contribution of high baseflow in November 2010, but it didnÃ‚Â’t cause flood since the TRO was low.